Estimation Of Welding Wire Requirements (Electrode) For Installation Of 300 Feet Barge Sideboard Assembly - Langgeng , Diana; Mujiarto, Iman (Nama Jurnal Akmi, 2024)
Installation of the sideboard assemblies on a 300 feet barge requires an estimate of the need for welding wire, besides that an estimate of the need for oxygen and LPG gas is also required for the work of cutting the old sideboard. This is so that the repair work does not experience errors in estimating the amount of consumables used so as not to result in losses for the shipyard company. The objectives obtained during the research were to determine the need for welding wire in the welding process of the 300 feet barge sideboard. The design of this study uses a quantitative approach and there are several variables used including independent variables such as the thickness of the material, the length of the welding, and cutting areas. Dependent variables such as the number of electrodes, oxygen, and LPG gas used. Control variables such as the SMAW welding process using AWS A5.1 E6013 electrodes and cutting using an oxygen and LPG gas cutting blender. The data collection techniques in this study were literature study, observation, and interviews. Based on the calculation, the total need for welding wire for the installation of the 300 feet sideboard assembly is 95.87 kg total oxygen requirement of 241.51 kg and LPG gas of 177.35 kg for cutting the old sideboard.